(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Most acute coronary presentations are caused by non-ST-elevation acute coronary syndromes (NSTE-ACS), which include non-ST-elevation myocardial infarction (NSTEMI) and unstable angina (UA). The severity of these conditions varies significantly. Although the Thrombolysis in Myocardial Infarction (TIMI) risk score is a validated bedside tool for risk stratification, its association with the angiographic severity of coronary artery disease (CAD) has not been sufficiently investigated in the Indian population. The purpose of this study was to ascertain whether the degree of coronary vascular involvement in individuals with NSTEMI and UA was correlated with the TIMI risk score. Methods: This retrospective observational record-based study was conducted among 98 patients diagnosed with NSTEMI or UA who underwent coronary angiography at a tertiary care center in Puducherry, India, between January 2024 and June 2025. Patient data were extracted from medical records using ICD-10 codes and validated proformas. TIMI scores were calculated using seven clinical and laboratory parameters and categorized as <4 (low–moderate risk) or ≥4 (high risk). Coronary angiography findings were reviewed to classify vessel involvement as single-vessel (SVD) or multi-vessel disease (MVD). Statistical analysis included chi-square test, odds ratio (OR) estimation, and multivariate logistic regression to identify independent predictors of MVD. Results: The patients were 69.4% male and had a mean age of 61.8 ± 9.3 years. The most prevalent risk factors were diabetes mellitus (55.1%) and hypertension (62.2%). Coronary angiography showed SVD in 36 patients (36.7%) and MVD in 59 patients (60.2%). Those with TIMI ≥4 had a considerably higher prevalence of MVD than those with TIMI <4 (78.7% vs. 45.1%, p = 0.001). A 4.59-fold higher risk of MVD was linked to a high TIMI score (95% CI: 1.84–11.43). The TIMI ≥4 category continued to be an independent predictor of MVD after controlling for age, diabetes, hypertension, and smoking (adjusted OR = 3.92, 95% CI: 1.42–10.83, p = 0.008). Conclusion: A strong and independent association was observed between the TIMI risk score and the angiographic extent of coronary vessel involvement in NSTEMI and unstable angina. Patients with higher TIMI scores were significantly more likely to have multi-vessel coronary artery disease. The TIMI score, being simple and cost-effective, can be used as an effective triage tool for identifying high-risk patients who may benefit from early invasive management, particularly in resource-limited settings.